Declining Ungulate Populations in an African Rainforest: Evidence From Local Knowledge, Ecological Surveys, and Bushmeat Records - Kamgaing, Towa Olivier William; Dzefack, Zeun's Célestin Brice; Yasuoka, Hirokazu (Frontiers in Ecology and Evolution, 2019)
Sound wildlife management requires an awareness about the trends in animal composition and abundance by all stakeholders, including local peoples. Hunters (n = 255) from two adjacent community hunting zones (CHZ) in southeast Cameroon were interviewed about the species composition of the animals killed using snare traps between 1952 and 2015–2016 and the drivers of change. The comparison of the perceived spatial and temporal trends in game composition to those from transect surveys and bushmeat records conducted in the area since the nineties evidenced the followings: (1) hunters are aware of the coarse changes in prey abundance, even for the species for which population density is difficult to estimate using more conventional survey methods; (2) in southeast Cameroon and in forests regions with similar fauna, the bay duiker (Cephalophus dorsalis) and the Peter's duiker (C. callipygus) are clearly more abundant than the white-bellied duiker (C. leucogaster) and black-fronted duiker (C. nigrifrons); (3) the two sites surveyed are at different stages of prey depletion, and (4) perception of prey composition is consistent with village-based bushmeat records and is likely to reflect more the species compositions in anthropogenic forest mosaics, where hunting is more frequent. Hunters' interviews constitute a valuable means to rapidly assess the status and trends in animal populations. However, the discrepancies between perceptions and prey composition in remote forest areas, combined with the assumption that shifting baseline syndrome is operating, highlight the need of caution when using local knowledge to generalize trends in fauna assemblages over large geographical and temporal scales.